2010
DOI: 10.1021/jp1093096
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Response of Semiconductor Nanocrystal-Dye Sensors: The Case of pH

Abstract: Emissive semiconductor nanocrystals can be efficient FRET donors to chemically responsive organic fluorophores; conjugating the two creates a ratiometric (or self-calibrating) sensor. Given that the organic component engenders chemical and/or biological sensitivity, it is natural to assume that the NC-dye response is reflective of the photochemical properties of the neat dye. In the case of a pH sensor like fluorescein, the dye emission can be analytically described by the Henderson-Hasselbalch equation. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The blue-shift of the NC emission at low dye-loading levels is likely due to differential FRET efficiency across the NC emission profile as recently demonstrated; 4748 furthermore, the blue-shift of the dye acceptor emission is due to the narrow excitation window from the NC donor. 49 …”
Section: Resultsmentioning
confidence: 99%
“…The blue-shift of the NC emission at low dye-loading levels is likely due to differential FRET efficiency across the NC emission profile as recently demonstrated; 4748 furthermore, the blue-shift of the dye acceptor emission is due to the narrow excitation window from the NC donor. 49 …”
Section: Resultsmentioning
confidence: 99%
“…[18–19] Several groups have exploited QD-based approaches to measure cellular pH. [20] Medintz et al reported that QD-dopamine conjugates were pH-responsive by the redox abilities of the conjugated dopamine dye (Figure 2). [20a] The surface of CdSe/ZnS QDs (λ em = 550 nm) were coated with hexahistidines that are covalently attached by dopamines.…”
Section: Cell-based Biosensorsmentioning
confidence: 99%
“…Krooswyk et al [ 89 ] studied the response mechanism of this QD-sensing dye motif using a CdS/ZnS-fluorescein pH sensor. They initially proposed that the response mechanism should be dictated only by organic dye’s photochemical properties.…”
Section: The Response Mechanisms Of Qd-based Fret Sensors: Spectramentioning
confidence: 99%